Peran Vital Hamba Tuhan Dalam Memimpin Jemaat Menuju Kesehatan Rohani - MerryWaty Gulo; Aprianus Ledrik Moimau (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The vital role of God's servant in leading the congregation towards spiritual health. God's servant has an important responsibility in leading the congregation towards spiritual health in building a strong community in Christ. God's servant plays a leadership role in directing the congregation towards spiritual health. Spiritual health is an important goal in the life of a quality church that involves providing accurate teaching, encouraging congregations to study God's Word, and helping to apply the principles of faith in daily life.